Application of the Eco-Epidemiological Method in the Study of Leishmaniasis Transmission Foci (2017)
ABSTRACT: The study of transmission foci involves the clinical characterization of disease within a focus using active surveillance of human cases, characterization of the population group that is most frequently infected or at highest risk of becoming infected, diagnosis and treatment of infected people and identification of the conceptions, attitudes, beliefs and practices related to the disease. An entomological survey is necessary to determine the geographical distribution of species and incrimination of vector species, the ecological characteristics of the zone (macro-focus), times of the year and day of highest biting activity and places in homes in which the most frequent contact between the people and the vectors occurs. A survey of peri-domestic and wild mammals in the area is advisable to try to identify potential reservoir hosts. Using this information, it is feasible to design specific and accurate prevention and effective, rational and economic control measures and define the times of the year and locations in which these measures must be applied. In this chapter, a description of the application of the eco-epidemiological method to the study of leishmaniasis transmission foci is provided. A special emphasis is placed on the methodology, multidisciplinary work and analysis of findings.